Lafarga, F. & Pegenaute, L. (Eds.) (2016). Autores traductores en la España del siglo XIX. Kassel: Reichenberger. - Paz-Soldán, Rosario Valdivia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2018)
/